Evaluating Fresh Earthworm as an Alternative Feed for the Spiny Lobster Panulirus homarus: Growth and Immune Responses - Fawzan Bhakti Soffa; Muhammad Firdaus; Sunarti Sinaga (Marine Science Department Diponegoro University, 2026)
Limited feed availability is one of the major challenges in scaling up lobster aquaculture in Indonesia. At present, most lobster farmers rely heavily on trash fish, mainly sardines, which are nutritionally unbalanced, compete with human consumption, and are subject to seasonal fluctuations in price and availability. This study evaluated the use of earthworms as an alternative feed for juvenile scalloped spiny lobster (Panulirus homarus), assessing their nutritional value and effects on growth, survival, and immune responses. A 63-day feeding trial was conducted with four treatments and three replicates per treatment: 100% fish (Control), 70% fish + 30% earthworm (R7C3), 30% fish + 70% earthworm (R3C7), and 100% earthworm (C10). Hemolymph samples were collected to analyze total hemocyte count (THC) and phenoloxidase (PO) activity alongside growth measurements. Lobsters fed earthworm-based diets (C10, R3C7, and R7C3) exhibited significantly higher specific growth rates (0.98–1.73%/day) compared with the control (0.42–0.59%.day-1). Survival followed a similar pattern, with markedly higher rates in earthworm-fed groups (60–75%) than in the control ( 25%). Immune parameters, including THC and PO activity, were significantly elevated in lobsters receiving earthworm diets. These findings demonstrate that earthworms are a promising, sustainable feed alternative that improves growth, survival, and immunity in P. homarus, reducing dependence on trash fish in lobster aquaculture.